THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF A HOLISTIC PROCESS OF MUSICAL RESEARCH AS A CONDITION OF DEVELOPMENT PERSONALITY'S MUSICAL THINKING - Г. Нагорна (Київський національний університет імені Тараса Шевченка, 2018)
The article presents the theoretical and methodological foundations of a holistic process of musical research, providing the development of musical thinking of masters. In this regard, strategic and tactical approaches to the research of musical thinking of the individual were developed. At the same time the rational-creative research approach was the leading methodological foundation of the holistic process of the emergence and formation of musical thinking among masters. In other words, the research became a methodology of musical education, since on its basis and in its process the development of musical thinking of music teachers has occurred. In the course of this research, future musicians in their professional activities achieved rational creativity. With the help of the system approach, the structural basis was provided both for studying the musical thinking of the individual and for the holistic musical process. The theoretical basis was the criterial-value approach to the assessment of the musical thinking of masters, as well as to a holistic research of their musical art. These theoretical preconditions have been practically realized with the help of a personality-activity approach to future musicians in the process of their interaction with subjects, phenomena of musical art. Consequently, the system of relations between informing and stimulating situations of interactions with subjects, phenomena of musical art was the object of the research of masters. This system was developed on the basis of the unity of the systemic, criterial-value and personality-activity approaches presented under the aegis of the rational-creative approach.The generalized mental actions mastered by the masters in the process of a holistic of musical research were: the skill to select the goal of musical research; the skill to find or creatively build up tactics of relations that arise in the process of interaction with the subjects of musical research; the skill to elaborate a value-methodological strategy; the skill to assess, self-evaluate the relevance, reliability, strength of the developed strategy and tactics of the relationship of the holistic process of musical research.The factors determining the development of the musical thinking of the masters were identified such as: interest in activity of musical research; the need to engage in it and the vocation for it; qualities of personality, necessary to musician-teacher-performer; knowledge of peculiarities of the development of musical art; skills: constructive, organizational, communicative, gnostic.Thus, on the one hand, the achievement of the professional reasonableness of the musician in the process of research the holistic musical process is ensured. On the other hand, the basic ideas of the concept of the formation of the musical thinking of the personality are realized, which consist in the fact that the formation of the designated thinking is determined by the dialectical unity of generalized mental actions that constitute the essence and content of this thinking, the factors that influence its development, and the system of strategic and tactical approaches necessary for its implementation.As a result, the system of professional university training has been transformed taking into account approaches to: musical education as a research of the holistic musical process; researching as the self-critical activity of a future musician; a musician as a special person who takes a subjective position, and creates polysubject (dialogical) relations in the course of mutual communication.

Представлено теоретико-методологічні основи цілісного процесу музичного дослідження, що забезпечують розвиток музичного мислення магістрів. Розроблено стратегічні і тактичні підходи до дослідження музичного мислення особистості.При цьому провідною методологічною основою всього процесу виникнення і формування в магістрів музичного мислення був раціонально-творчий дослідницький підхід. Дослідження стало методологією музичної освіти, оскільки на його основі та в його процесі відбувався розвиток музичного мислення педагогів-музикантів. Об'єктом дослідження магістрів виступала система відношень інформаційних і стимулювальних ситуацій взаємодій із предметами, явищами музичного мистецтва, що розроблена на основі єдності представлених системного, критеріально-ціннісного й особистісно-діяльнісного підходів під егідою раціонально-творчого підходу. Таким чином, з одного боку, забезпечено досягнення професійної розумності музиканта в ході дослідження ним цілісного музичного процесу, з іншого, – реалізовані провідні ідеї концепції формування музичного мислення особистості, які полягали в тому, що формування зазначеного мислення детерміновано діалектичною єдністю узагальнених розумових дій, які є сутністю та змістом цього мислення, факторів, що впливають на його розвиток, а також системою стратегічних і тактичних підходів, необхідних для його реалізації. Унаслідок чого перетворена система професійної підготовки у вищому закладі освіти з урахуванням підходів до музичної освіти як до дослідження цілісного музичного процесу, дослідження як самокритичної діяльності майбутнього музиканта, музиканта як до особливої особистості, яка займає суб'єктну позицію і сама створює полісуб'єктні (діалогічні) відносини в ході взаємоспілкування.
ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ ОСНОВИ ЦІЛІСНОГО ПРОЦЕСУ МУЗИЧНОГО ДОСЛІДЖЕННЯ ЯК УМОВА РОЗВИТКУ МУЗИЧНОГО МИСЛЕННЯ ОСОБИСТОСТІ
Keywords: музичне мислення; професійна розумність; дослідження; musical thinking; professional reasonableness; research